Анализ и предложения по организации подготовки инженеров – преподавателей-электроэнергетиков в Украине - Шевченко, Валентина Владимировна; Лизан, Игорь Ярославович (Наука и технологии, 2012)
Состояние энергетики в современном мире требует непрерывного исследования и внедрения новых технологий. Развитие любой отрасли определяется уровнем подготовки кадров. Поэтому особое внимание следует уделять профессиональной компетенции будущих инженеров – преподавателей-энергетиков, определению роли практической направленности их подготовки, контролю их знаний, умению видеть технические проблемы, разрешать их с учетом современных возможностей науки и техники.

The state of energy in a modern world requires continuous research and introduction of new technologies. Development of any industry is determined by the level of the personnel training. So it is necessary to spare the special attention to professional jurisdiction of future engineers - teachers-engineering specialists, to determination of role of practical orientation of their preparation control of their knowledge, ability to see technical problems, settle them taking into account modern possibilities of science and technique.
The analysis and suggestions from organization of preparation the engineers – teachers-engineering electro-specialists in Ukraine
Keywords: педагогика; компетентность профессиональная; подготовка специалистов; подготовка практическая; деятельность инновационная; деятельность проектная; энергосбережение; electroenergy; engineering pedagogies; professional competence; practical preparation; innovative activity; project activity; conservation of energy